Development of Nonlinear Adaptive PI Controller For Improved Pneumatic Actuator System - Samsudin, S. I; Sulaiman, Siti Fatimah; Osman, Khairuddin; Salim, S. I. M.; Mohd Azam, Sazuan Nazrah (International Journal of Integrated Engineering, 2022)
The wide application of pneumatic actuator in electrical and electronics sectors are undeniable hence ask for a good control environment. PID controller is always known with easy implementation and good control performance. But the limitation of the PID static gains to effectively control the complex nonlinear system is unavoidable. This suggests the enhancement of the PI controller with a nonlinear adaptive interaction algorithm (AIA). The modification is introduced by integrating a nonlinear gain function that adaptively tunes the AIA parameter, hence resulting the best tuning of the PI control gains. The uncertainties and nonlinearities inherent in the system parameters are believed to be handled by the integration, therefore improving the controller performances while maintaining the pneumatic actuator at the desired position. It was proved that improved error performance criteria’s, settling time and overshoot were resulted by the nonlinear AIA PI compared to fix AIA PI. Besides, the nonlinear AIA PI has successfully reduced the overshoot to 5.35% and 6.70% compared to optimal AIA PI and optimal PI controller, respectively. To conclude, the development of the proposed controller is demonstrated to function well and offers an alternative tuning strategy in other electronical and electronic engineering applications.